Phosphatidylinositol transfer protein-α in platelets is inconsequential for thrombosis yet is utilized for tumor metastasis. Issue 1 (December 2017) - Zhao, Liang; Thorsheim, Chelsea; Suzuki, Aae; Stalker, Timothy; Min, Sang; Lian, Lurong; Fairn, Gregory; Cockcroft, Shamshad; Durham, Amy; Krishnaswamy, Sriram; Abrams, Charles
Abstract Platelets are increasingly recognized for their contributions to tumor metastasis. Here, we show that the phosphoinositide signaling modulated by phosphatidylinositol transfer protein type α (PITPα), a protein which shuttles phosphatidylinositol between organelles, is essential for platelet-mediated tumor metastasis. PITPα-deficient platelets have reduced intracellular pools of phosphoinositides and an 80% reduction in IP3 generation upon platelet activation. Unexpectedly, mice lacking platelet PITPα form thrombi normally at sites of intravascular injuries. However, following intravenous injection of tumor cells, mice lacking PITPα develop fewer lung metastases due to a reduction of fibrin formation surrounding the tumor cells, rendering the metastases susceptible to mucosal immunity. These findings demonstrate that platelet PITPα-mediated phosphoinositide signaling is inconsequential for in vivo hemostasis, yet is critical for in vivo dissemination. Moreover, this demonstrates that signaling pathways within platelets may be segregated into pathways that are essential for thrombosis formation and pathways that are important for non-hemostatic functions. Platelets support tumor metastasis formation. Here, the authors show that the phosphoinositide signaling modulated by PITPα is essential for platelet-mediated tumor metastasis signaling, but surprisingly it is dispensable in hemostasis in mice.